EVALUATION OF REALIZED INVESTMENTS IN AGRICULTURE IN AREA OF UPPER DANUBE REGION - Subić, Jonel; Jovanović, Marijana; Potrebić, Velibor (Economics of Agriculture, 2012)
Special natural reserve "Upper Danube" is protected natural area I category, which extends on the left bank of Danube river in Republic Serbia. The reserve is part of large marshland complex and represents one of the last large floodplains on the ground of the European continent. Getting into consideration the natural conditions, production resources, the structure of agricultural production and related activities, and environmental, infrastructural and social conditions in which these economic activities take place, formed the basis for research on the Upper Danube. For research purposes, this feld is viewed in the broader context of the administrative area includes the city of Sombor and Municipalities: Apatin, Bač and Bačka Palanka. On the other hand, from the perspective of the enlargement process of the European Union (EU), derived for our country and the importance of capital investment for sustainable development imposed by the need to analyze the economic effciency of investment in agriculture. Accordingly, the research activity is conducted within the boundaries of the analysis of investments in agriculture in the Upper Danube.